VoIP : wireless, P2P and New Enterprise Voice Over IP - Ganguly, Samrat (Wiley, 2008)
Understand how new network technologies impact VoIP!. Voice over Internet Protocol (VoIP) is revolutionizing the way people communicate - both in the corporate world and in personal life. The enormous success of VoIP has led to its adoption in a wide range of networking technologies. Each network technology has its unique features and poses distinct challenges for the performance of VoIP. VoIP: Wireless, P2P and New Enterprise Voice over IP describes the issues arising in the deployment of VoIP in an emerging heterogeneous network environment. Along with a brief overview of the concepts, proto.